Understanding school frontline workers’ early implementation behavior: insights from the generation healthy kids study in Denmark - Jonas Vestergaard Nielsen; Sofie Koch; Tine Hyldahl Henriksen; Rikke Fredenslund Krølner; Line Lund; Louise Ayoe Sparvath Brautsch; Line Kattai Ulrikkeholm; Camilla Trab Damsgaard; Malte Nejst Larsen; Thomas Skovgaard (Frontiers in Sports and Active Living)
IntroductionChildhood obesity is a growing global public health issue, with significant implications for children’s physical and psychological well-being. Schools offer a structured environment for implementing health-promoting interventions to address this challenge. This study examines how organizational conditions within schools influence frontline workers’ (e.g., teachers and pedagogic staff) early implementation behavior in a school-based health intervention. Insights aim to inform strategies for enhancing the sustainability and effectiveness of such programs.MethodsThe study utilizes a qualitative design, conducting 11 focus group interviews across 11 of the 12 intervention schools participating in the Generation Healthy Kids (GHK) intervention program in Denmark. Using the Consolidated Framework for Implementation Research (CFIR) and the COM-B Model for Behavior Change, the interviews explored organizational factors shaping frontline workers’ capabilities, opportunities, and motivation for implementing GHK components. Thematic analysis, guided by predefined theoretical constructs, was applied to identify key patterns in the data.ResultsThe findings highlight organizational conditions within schools as critical to frontline workers’ early implementation behavior. Capability was linked to training and resources, though time constraints hindered effective application. Opportunity was shaped by structural factors such as limited access to facilities, causing logistical challenges. Motivation was influenced by alignment with existing workflows, reflective beliefs about the program’s relevance, and tension for change due to perceived pupil needs. Leadership emerged as a cross-cutting factor, with engaged leaders enhancing implementation through active support and resource coordination.DiscussionThe study underscores the interplay between organizational conditions and frontline workers’ behaviors in implementing health programs. Addressing logistical barriers, fostering supportive leadership, and ensuring alignment with school priorities are essential for successful implementation. These findings highlight the need for adaptive, school-specific implementation strategies to sustain health-promoting interventions like GHK and suggest stakeholder engagement to further optimize implementation processes.